HUBUNGAN SOSIAL-POLITIK TAREKAT SAMANIYAH DENGAN KESULTANAN PALEMBANG DARUSSALAM - Ravico Ravico (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2018)
Abstract: The Sammaniyah Order was the largest in the archipelago and became the driver of jihad fi sabilillah against the Dutch colonial. The involvement of the Sammaniyah Congregation in the political world has denied various views that claim the tarekat as the bearer of setbacks and chaos. This reason is the basis of this tarekat and political study. To find answers to the grand problem of the relationship between the Sammaniyah Congregation and the Palembang Darussalam Sultanate, historical research methods are used with steps such as heuristics, verification, interpretation and historiography. This study can conclude that between the Sammaniyah Congregation and the Palembang Darussalam Sultanate had a very close relationship the Palembang Darussalam Sultanate was the protector of the congregation in the sultanate region so that the religious system in Palembang would continue, while the Sammaniyah Congregation as the community elite became a driver of Islamic practice.